PKM EDUKASI PENTINGNYA PHYSICAL ACTIVITY DALAM MENINGKATAN DAYA TAHAN JANTUNG PARU PADA SISWA SMA - Boki Jaleha; Kuswardani Kuswardani; Zainal Abidin; Suci Amanati; Novita Alfiani; Irawan Wibisono; Maya Triyanita; Didik Purnomo; Luhur Sesanti (JPMUJ, 2025)
This community service aims to educate high school students on the importance of physical activity in improving their cardiorespiratory endurance. The activities were carried out in two schools: SMAN 6 Wajo and SMKN 7 Semarang. Methods include presentations, demonstrations, discussions, and pre-post evaluations using IPAQ (International Physical Activity Questionnaire). Results showed increased understanding in both schools with pretest-posttest scores rising significantly. This indicates a successful improvement in awareness and knowledge about appropriate physical activity for cardiorespiratory fitness.